Climate Change: Eco-Dystopia in Antonio Scurati’s La seconda mezzanotte - Chiafele, Anna (Quaderni d'Italianistica)

(untitled) (Iter Press, 2021)
This article offers an examination of the novel La seconda mezzanotte (2011) by Antonio Scurati. Classified by the author as a catastrophist sci-fi novel, this work is here defined and analyzed as one of the very first Italian examples of climate fiction (cli-fi), a narrative form especially popular in North America, closely related to anthropogenic climate change. The essay discusses some of the topoi that characterize Anglo-Saxon cli-fi, which are clearly present in The Second Midnight. Such recurring motifs will also be discussed, in particular, by highlighting some of the rhetorical tools adopted by Scurati, such as, for example, the effect of estrangement. Through such effects, the reader is spurred to adopt an uncomfortable, “oblique” and unusual gaze. This study highlights Antonio Scurati’s skill and originality in dealing with the causes and global effects of climate change. The author succeeds in making the reader perceive the spatial and temporal magnitude of global warming, which in 2072 Venice materializes dramatically in a Big Wave. The Second Midnight is a human comedy that expands across centuries and continents while narrating the events of a few men living in Nova Venezia in a specific year, 2092. Distant spaces, remote times, human and non-human corporealities converge in a new Venice, which is a piece of a hologram narrating other people’s stories.